Effect of Beta Thalassemia Trait in Pregnancy - Roy, Marlina; Robbani, Md Golam; Karim, Rahnuma; Hasan, Nasrin (Community Based Medical Journal, 2024)
A cross-sectional, observational study was conducted to determine the effects of beta thalassemia trait in pregnancy. A total of 150 pregnant women diagnosed with beta thalassemia trait in Bangladesh Navy Ship (BNS) Patenga Hospital, at Chattogram, Bangladesh, having regular antenatal care and delivery, between January and December of 2022, were included in the study. Thalassemia status was diagnosed by Hb-electrophoresis. Most of the patients belonged to the age group 19-35 years. 30.46% of women had normal hematocrit level. During pregnancy women suffered from severe anemia (14%) and mild anemia (55.33%) (P<0.001). Blood transfusion needed during 1st trimester (1.3%), 2nd trimester (4.6%), 3rd trimester (8%) and at postpartum period (9.3%) (P>0.05). Most of the women (76.66%) delivered babies at her 36-39 weeks of gestational age,18.67% delivered at or after 40 weeks of gestation and 4.67% delivered baby before 36 weeks (P<0.05). 66.67% had normal vaginal delivery, while 33.33% underwent Caesarean section operation due to several complications. Observed obstetric complications were: pregnancy induced hypertension (6.6%), gestational diabetes (4%), oligohydramnios (11.33%, premature rupture membrane (3.3%), preterm labor (8.66%), and placental abruption (1.33%). Adverse fetal outcomes observed were: prematurity (4.6%), intrauterine growth retardation (5.33%), still birth (0.6%), and fetal asphyxia (3.33%). Neonatal admission at NICU was needed in 2(1.33%) cases. CBMJ 2024 January: vol. 13 no. 01 P: 77-82